A Study on Translator's Subjectivity from the Perspective of Feminist Translation - Di Zhang, Lulu Cheng, Yanyun Li (Forest Chemicals Review, 1970)
In the study, we analyze feminism works of Virginia Woolf's A Room of One's Own from the perspective of translators' subjectivity on the basis of feminist translation theory by using Flotow's three kinds of feminist translation methods, namely supplementing, prefacing and footnoting, and hijacking. We also explore the ingenious fusion of feminist translation view and translator's subjectivity, aiming at providing new ideas for how to reproduce the female image and highlight the translator's dominant position.